Drivers of customer equity in the South African sports utility vehicle market - Pereira, Pedro (My University, 2013)
The South African vehicle market is on the way to recovering from the effects of the global financial crisis. Vehicle manufacturers are under pressure to increase sales volumes in an environment where more brands and models are entering the market, and the year on year sales growth is declining. Marketers need to focus their strategies around a customer-focused approach to Customer Equity as opposed to the traditional product-focused approach. Improving their Customer Equity will allow manufacturers to become more competitive and increase the lifetime value of their current and future customers. The purpose of this study is to identify the drivers of customer equity in the South African sports utility vehicle (SUV) market. The main objective is to identify the drivers and sub-drivers of Customer Equity together with their relative importance and to evaluate the performance of the South African SUV brands against these drivers. The research follows a mixed method approach whereby the qualitative study together with the literature review makes up the measuring instrument that is used in the quantitative study. The quantitative study has a sample of 106 respondents who currently own and drive SUV’s. Respondents completed an online questionnaire from which data was collected on the importance and relative performance of SUV brands against the Customer Equity drivers. Descriptive statistics were used to analyse and interpret the data to draw conclusions. Three main groups of Customer Equity drivers were identified together with twenty underlying sub-drivers. Brand, Relationship, and Value are the main drivers with the Value driver carrying the highest importance for SUV customers.
MBA thesis
Keywords: Customer equity; Sports utility vehicles